Influential Factors for the Improvement of Peer Education in Adolescents: A Narrative Review - Marzieh Azizi; Zeinab Hamzehgardeshi; Zohreh Shahhosseini (Mazandaran University of Medical Sciences, 2017)
Context: Peer education is an effective strategy for improving adolescents' health. It focuses on the improvement of knowledge, attitudes and beliefs among adolescents with regards to different healthcare issues and empowers them to make informed decisions. This review study aimed to determine factors that promote peer education among adolescents. Evidence Acquisition: In this narrative review, electronic databases including Google Scholar, Science Direct, PubMed (including Medline), Web of Science, Scientific Information Database, and Scopus were searched. Articles published between 1991 and 2016 were retrieved and undergone abstract and full-text appraisal. Lastly, 53 articles were selected and used to write this review. Results: The factors influencing the promotion of peer education among adolescents were classified as follow: 'characteristics of peer educators': personal, skills and communication characteristics; 'characteristics of the educational program': theoretical foundations, program transparency, program sustainability, adolescents' comprehensive participation, and evaluation and monitoring; and 'structural characteristics of the educational program': supportive structure, and financial-official structure. Conclusions: Taking into account the importance of adolescence and issues surrounding this period, the important role of peer education in the promotion of adolescents' health should be emphasized.